Pseudo Expertise: Tantangan dan Peluang Pendidikan Agama Islam di Era 5.0 (Pusat Riset dan Inovasi Nasional, 2026)
The phenomenon of pseudoexpertise on social media, namely the tendency to feel knowledgeable without adequate scientific grounding due to exposure to unrestricted information, has become a serious challenge for Islamic religious education. This study employs a phenomenological method through in-depth interviews with two Master's students of Islamic Education (PAI) at UIN Syarif Hidayatullah Jakarta, who come from different social backgrounds teaching at Islamic boarding schools in rural Bogor and urban South Jakarta to obtain diverse perspectives on how social context influences the emergence of pseudoexpertise. The selection of master's-level informants is based on their academic qualifications and teaching experience, which are considered capable of providing representative insights. Secondary sources include scientific articles and relevant literature. The findings indicate that globalization and pseudoexpertise constitute obstacles that are difficult for religious teachers to control, as students acquire much of their religious knowledge from outside the school without verification. Therefore, contextual Islamic Education (PAI) learning and teachers who serve as knowledge validators through healthy communication are required, enabling students to filter information and develop more mature religious literacy.